EFFECTS OF COMPUTER VISION SYNDROME ON TEAR FILM QUALITY OF INDIVIDUALS ACROSS VARIOUS AGE GROUPS AND OCCUPATIONS - CHOUHAN, DEEPIKA; PARMAR, BHAWNA; OJHA, BIMALESH; KHANDELWAL, GARVITA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Computers become a part of everyday life because it has to a greater extent, revolutionized most professions and their work performance. Spending uninterrupted and excessive time in computers and other display devices without taking precautions and prevention leads to significant ocular problems, which are being grouped together as - computer vision syndrome (CVS). The present study was conducted in a tertiary care center to evaluate the effects of CVS on tear film quality in individuals across various age groups and occupations. Methods: A cross-sectional study was conducted at a teaching institute from August 2021 to September 2022, in which 600 patients who worked on computers or digital devices for at least 3 h daily were included in this study. In all patients, a complete ocular examination was performed, including visual acuity, refraction, Schirmer’s test 1, tear film breakup, slit-lamp examination, intraocular pressure, and fundus examination by indirect ophthalmoscopy. Results: In the present study, most of the participants in this study belonged to 21–30 years of age. Among study participants with CVS and screen time of more than 8 h, 88% had moderate and severe dry eyes. On comparison of mean values of the Schirmer’s test between participants with CVS, it was observed that mean Schimers (4.5 mm in the right eye and 5 mm in the left eye) and tear film breakup time (4.9) were much lower among study participants with CVS whose screen usage time was more than 8 h. Conclusion: The present study found that computer vision conditions are very common. In addition, the likelihood of developing the same was higher among IT employees and engineering students.